Evaluating the Effectiveness of Soft Skills in College Accounting Education - Hernández, Diego Fernando (Journal of Posthumanism, 2025)
Incorporating soft skills into accounting education is essential for career success, improving communication, critical thinking, and ethical decision-making. This study evaluated the effectiveness of developing these competencies in university accounting programs. It used a mixed approach, combining quantitative and qualitative methods, with a sample of 300 final-year students and 30 accounting professors from three universities in Medellín, Colombia. Data were collected through surveys, semi-structured interviews, and documentary analysis. The results revealed that although most students and teachers recognize the importance of soft skills, few consider them to be taught effectively. 70% of students value these skills, but only 45% believe that their teaching is adequate. Among teachers, 80% appreciate these skills, but only 25% feel prepared to teach them and 40% perceive sufficient institutional support. It concludes that there is a need to integrate soft skills more effectively into accounting programs through innovative pedagogical approaches, continuous teacher training, and increased resource allocation. In addition, to promote close collaboration with the professional sector by aligning educational programs with the needs of the labor market.